Consumer Behavior And Marketing Strategies In Blind Box Commerce: A Systematic Literature Review - Ummu Savira Maulida Akhmad; Budi Astuti (Equivalent : Journal of Economic, Accounting and Management, 2026)
The blind box commerce phenomenon is rapidly growing as an uncertainty-based marketing strategy that combines elements of surprise, gamification, and collectibility value. This model has been proven to trigger curiosity, emotional arousal, and impulsive buying, especially among Gen Z, who are highly responsive to hedonistic experiences and visual branding. Although research on blind boxes is increasing, there has been no systematic review that integrates various theoretical and empirical perspectives to understand the psychological mechanisms and effectiveness of this marketing strategy. This study conducted a Systematic Literature Review (SLR) of 30 studies published between 2020 and 2025 to map the determinants of consumer behavior, the role of uncertainty, perceived value, scarcity, and social dynamics in blind box consumption. The analysis results show four main findings: (1) uncertainty drives curiosity, instant gratification, and cognitive biases such as gambler's fallacy; (2) perceived value, including emotional, symbolic, and social value, is a strong mediator in purchase and repurchase intention; (3) marketing strategies such as scarcity, IP licensing, and gamification increase engagement and urgency to purchase; and (4) there are ethical risks such as overspending, anxiety, and potential addiction in vulnerable groups. This study offers an integrated conceptual framework based on SOR, Uncertainty Curiosity Theory, Perceived Value Theory, and Scarcity Theory, and provides practical implications for brands and regulators to develop more ethical, effective, and sustainable blind box marketing.